Digital Divide dalam Adopsi Mobile Banking di Kota Purbalingga: Suatu Kajian - Ghaniyyah, Az Zahra Sekar; Giri, Refi Rifaldi Windya (Universitas Batanghari Jambi, 2024)
One sign of progress in the banking industry is the creation of mobile banking services that provide convenience for customers. However, the use of mobile banking is not evenly distributed in all regions, one of which is Purbalingga City which still has minimal use of digital transactions, especially mobile banking. This research aims to find out whether there is a digital gap regarding the use of mobile banking in Purbalingga City. This research uses digital divide variables consisting of motivation, physical & material access, mobile banking skills and also usage, using quantitative methods using PLS-SEM as a data analysis technique. The sampling technique used in this research is nonprobability sampling with purposive sampling. Data collection uses secondary data and primary data through distributing questionnaires. This research consists of 301 samples taken from the population of the Purbalingga City community who use mobile banking. The results of this research show that there are 4 (four) latent variables consisting of motivation, physical and material access, as well as skills and use of mobile banking have a positive and significant effect on the use of m-banking in Purbalingga City.